1977
DOI: 10.1177/004912417700600102
|View full text |Cite
|
Sign up to set email alerts
|

Notes On the Contamination Method

Abstract: The contamination method of obtaining confidential information was compared to more standard methods of interviewing, with the criterion being the degree to which the methods elicited candid responses. Two experiments were conducted in which college students were asked whether or not they had engaged in a variety of behaviors which were illegal, immoral, and/or embarrassing to admit. The results of both studies showed no differences between the interviewing methods in affirmation rates. A plausible explanation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

1982
1982
2023
2023

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(3 citation statements)
references
References 1 publication
0
3
0
Order By: Relevance
“…A Census Bureau study in the 1990s determined that promises of confidentiality had no significant effect on response rates (Dillman et al 1996). Moreover, experimental studies have consistently found that assurances of confidentiality can actually increase concerns about confidentiality and reduce response rates to surveys (Berman, McCombs, and Boruch 1977;Frey 1986;Reamer 1979;Singer, Hippier, and Schwartz 1992).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A Census Bureau study in the 1990s determined that promises of confidentiality had no significant effect on response rates (Dillman et al 1996). Moreover, experimental studies have consistently found that assurances of confidentiality can actually increase concerns about confidentiality and reduce response rates to surveys (Berman, McCombs, and Boruch 1977;Frey 1986;Reamer 1979;Singer, Hippier, and Schwartz 1992).…”
Section: Discussionmentioning
confidence: 99%
“…1996). Moreover, experimental studies have consistently found that assurances of confidentiality can actually increase concerns about confidentiality and reduce response rates to surveys (Berman, McCombs, and Boruch 1977; Frey 1986; Reamer 1979; Singer, Hippier, and Schwartz 1992).…”
Section: Discussionmentioning
confidence: 99%
“…Devices like coins (Barth & Sandier, 1976;Zdep & Rhodes, 1977), dice (Berman et al, 1977), and poker chips (Wiseman et al, 1975) are obviously more commonplace. A device's exoticism will depend somewhat on the local culture.…”
Section: Respondent-supplied Randomizersmentioning
confidence: 99%